Sunitinib in malignant melanoma: a treatment option only for KIT-mutated patients?. (December 2013) - Santini, Daniele; Vincenzi, Bruno; Venditti, Olga; Dell'Aquila, Emanuela; Maria Frezza, Anna; Silletta, Marianna; Guida, Francesco Maria; Grasso, Rosario Francesco; Silvestris, Nicola; Lanzetta, Gaetano; Tonini, Giuseppe
Sunitinib has previously been reported to be potentially effective in the treatment of malignant melanomas expressing c-KIT . Here we report on the case of a 77-year-old gentleman affected by a metastatic clear cell carcinoma of the kidney and a metastatic malignant melanoma with liver and lung metastases. Despite the negativity for CD117 and the absence of KIT amplification or mutations in the melanoma specimen, he achieved a partial response both in the lungs and in the liver while on sunitinib (50 mg once/day, 4 weeks on/2 weeks off) for the treatment of kidney cancer. To our knowledge, this represents the first evidence of sunitinib activity in KIT wild-type melanoma. Further studies should be performed to confirm these preliminary data.